DIFFERENT ASPECTS OF COMPLEXITY IN THE DOCTRINE OF MYSTICISM. - Tuychievna Tursunkulova, Shaxnoza (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2021)
In the article, the doctrine of mysticism was analyzed according to the theories of complexity, and the science of mysticism was considered to be a complex object. Its appearance, divided into different currents and directions, the essence of which was studied on the basis of synergistic concepts and principles. Scientific and philosophical aspects of mysticism were studied.